Mycobacterium haemophilum Masquerading as Leprosy in a Renal Transplant Patient. (28th November 2013) - Copeland, Nathanial K.; Arora, Navin S.; Ferguson, Tomas M.
Abstract : Opportunistic infections following immunosuppression in solid organ transplant (SOT) patients are common complications with the skin being a common sight of infection. Nontuberculous mycobacteria (NTM) are rare but potential causes of skin infection in SOT patients. We present a case of an adult male immunosuppressed following renal transplantation who presented with an asymptomatic rash for several months. The patient's skin eruption consisted of erythematous papules and plaques coalescing into an annular formation. After failure of the initial empiric therapy, a punch biopsy was performed that demonstrated nerve involvement suspicious for Mycobacterium leprae . However, culture of the biopsy specimen grew acid-fast bacilli that were subsequently identified as M. haemophilum . His rash improved after a prolonged course of clarithromycin and ciprofloxacin. Both organisms are potential causes of opportunistic skin infections and can be difficult to distinguish with similar predilection for skin and other biochemical and genetic similarities. Ultimately they can be distinguished with culture as M. haemophilum will grow in culture and M. leprae will not. This case was unique due to nerve involvement on biopsy which is classically seen on biopsies of leprosy.